The effect of nutritional status on the response to highly active antiretroviral therapy in human immunodeficiency virus-infected children at regional antiretroviral therapy centre in Northern India - Aaradhana, Singh; Ravi, Sachan; Vishnu, Mohan; Divya, Jain; Kriti, Mohan (Indian Journal of Child Health, 2018)
Background: Effect of highly active antiretroviral therapy (HAART) on growth in children is well established but influence of prior nutritional status on the response to HAART is not well known. Objective: To determine the influence of prior nutritional status on the response to HAART in terms of growth and CD4 counts. Methods: It was a retrospective record review based study conducted at a regional ART centre at a tertiary care, teaching hospital in Northern India. Human immunodeficiency virus (HIV) positive children who were naïve to antiretroviral therapy and were initiated on treatment from January 2006 to December 2007 were included in this study. Age, weight, height and CD4 cell counts were recorded at the initiation of HAART and after 24 months of therapy. Data was analyzed using paired t-tests within the groups, Chi-square tests, and one-way analysis of variance. Results: Seventy-nine HIV positive children were included in the study. At baseline, 29% of children were normal weight, 27% moderately underweight and 44% severely underweight with mean CD4 counts 243.30±178.50, 282.95±173.69 and 215.11±85.71 respectively. After 24 months of HAART, mean CD4 cell counts as well as weight for age z scores increased significantly in all 3 groups with mean CD4 counts being 913.61±401.46, 931.24±363.54 and 775.31±424.43 respectively in the groups. There were no significant differences in CD4 counts in the groups both pre and post ART. Conclusion: Underlying malnutrition does not adversely affect growth and immunologic response (increase in CD4 count) to HAART in HIV-infected children.